Sedimentology and geochemistry of Redang Island sediments, Terengganu - Sharifah Nur Faizah Syed Nooh (Fakulti Pengajian Maritim dan Sains Marin, 2012)
A study on the sediment characteristics and geochemistry of Redang Island sediment was conducted during pre and post-monsoon seasons. The sediments were collected around the Redang Island using UNIPERTAMA VII.